Trade with passion and purpose : - Whistler, Mark (John Wiley, 2007)
Some of the topics discussed include: How being "in the moment," while knowing why you are doing what you are doing is essential to trading success; The importance of understanding stress and how to work with it; The roles that affirmation and visualization playin your trading endeavors; How to recognize and defeat fear; ; How to develop a game plan for trading success that takes risk management into account; Why How world famous traders, sports stars, and business people handle stress, and how you can benefit from their successchange should be embraced, ect...